2002
DOI: 10.1046/j.1440-1614.2002.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Excitability of Psychiatric Disorders: Reduced Post-Exercise Facilitation in Depression Compared to Schizophrenia and Controls

Abstract: Post-exercise facilitation was reduced in depression and schizophrenia, suggesting impaired cortical excitability in these disorders. Further studies may discriminate between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…This observation, which has also been reported in schizophrenia (Reid et al., 2002; Chroni et al., 2002), might explain the symptoms reported by these patients, which can include fatigue, weakness, motor inertia, and apathy, and indicates the existence of a potentially strong relationship between psychiatric disorders and motor output.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This observation, which has also been reported in schizophrenia (Reid et al., 2002; Chroni et al., 2002), might explain the symptoms reported by these patients, which can include fatigue, weakness, motor inertia, and apathy, and indicates the existence of a potentially strong relationship between psychiatric disorders and motor output.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, a number of studies have shown that there is a significant decrease in postexercise facilitation in these individuals (Samii et al., 1996; Shajahan et al., 1999a, 1999b; Reid et al., 2002; Chroni et al., 2008) that is probably linked to an imbalance between inhibitory and excitatory inputs at the level of cortical-spinal neurons. This observation, which has also been reported in schizophrenia (Reid et al., 2002; Chroni et al., 2002), might explain the symptoms reported by these patients, which can include fatigue, weakness, motor inertia, and apathy, and indicates the existence of a potentially strong relationship between psychiatric disorders and motor output.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these authors recognized the limitation of considerable intersubject MEP amplitude variability. Moreover, the view that reduced postexercise facilitation is a neurophysiologic marker characteristic of the depressed state is weakened by findings suggesting that schizophrenic patients too, have similarly impaired facilitation (Chroni et al, 2002;Reid et al, 2002).…”
Section: Discussionmentioning
confidence: 99%